Analysis of the Implementation of Fixed Asset Accounting Based on PSAK Number 16 at PT Fortune Mate Indonesia Tbk - Andika, M. Sendi Feby; Putri, Novita Nurmala; Uzliawati, Lia (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
An important part of the financial statements are fixed assets, which require supervision and application of appropriate accounting in accordance with PSAK No. 16 for recognition, acquisition, depreciation, disposal and presentation. This research aims to evaluate how PT Fortune Mate Indonesia Tbk implements fixed asset accounting and the extent of their compliance with the provisions of PSAK No. 16. Descriptive qualitative methods were used in this research. The 2020-2022 financial report of PT Fortune Mate Indonesia Tbk is the subject of this research, with documentation techniques to collect secondary data. The research results show that PT Fortune Mate Indonesia Tbk applies fixed asset accounting in accordance with PSAK No. 16 to the fixed asset depreciation stage. However, a discrepancy was found in the presentation of fixed assets in the statement of financial position, where fixed assets were presented combined without details. In accordance with PSAK No. 16, fixed assets should be presented separately and in detail.